A Case of Brown-McLean Syndrome - Gökçen Gökçe; Volkan Hürmeriç; Osman Melih Ceylan (Türk Oftalmoloji Dergisi)
A 89-year-old man with a history of cataract surgery ten years ago presented to our ophthalmology department with blurred vision. On ophthalmic examination, best-corrected visual acuity was 20/50 in the right eye and 20/32 in the left. Slit lamp examination revealed bilateral symmetrical peripheral corneal oedema, advanced at the inferior part of the cornea in both eyes. Considering clinical and confocal microscopy findings, a diagnosis of Brown-McLean Syndrome (BMS) was made. BMS is a rare condition that may developed after cataract surgery, and it can be easily overlooked or misdiagnosed. Our report points to this rare syndrome and we tried to emphasis the importance of BMS considering it in the differential diagnosis of refractory peripheral corneal oedema developed in pseudophakic patients. (Turk J Ophthalmol 2013; 43: 365-7)